2019
DOI: 10.17308/kcmf.2019.21/1155
|View full text |Cite
|
Sign up to set email alerts
|

Инфракрасная Спектроскопия Как Метод Определения Структурных Откликов Природных Глин На Свч-Воздействие

Abstract: Методом ИК-спектроскопии изучены структурные отклики частиц монтмориллонитовой и каолинитовой глин месторождений Оренбургской области на СВЧ-воздействие. Обработку проб в течение 10 минут проводили в поле магнетрона мощностью 750 Вт в воздушной и влажной средах. Спектры получены с помощью ИК-Фурье спектрометра в диапазоне длин волн 4000–400 cм-1. Установлено, что в монтмориллонитовой глине количество доминирующих связей в тетраэдре SiO4 снижается в 1.5 раза при обработке в сухом воздухе и в 1.8 раза – во влажн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The locations of the extreme left lines of the manganese sextets in these positions coincided. Small discrepancies between the g-factors and the hyperfine coupling constants led to a shift in the positions of the remaining sextet lines and a [25,27,29] sequential decrease in their total amplitudes so that the right line of the spectrum (in a 'strong' magnetic field) split into two. Comparing the amplitudes of these components with the amplitude of the non-split line, it can be concluded that Mn 2+ ions were in two equally probable positions in the octahedral lattice, interacting with oxygen ions (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The locations of the extreme left lines of the manganese sextets in these positions coincided. Small discrepancies between the g-factors and the hyperfine coupling constants led to a shift in the positions of the remaining sextet lines and a [25,27,29] sequential decrease in their total amplitudes so that the right line of the spectrum (in a 'strong' magnetic field) split into two. Comparing the amplitudes of these components with the amplitude of the non-split line, it can be concluded that Mn 2+ ions were in two equally probable positions in the octahedral lattice, interacting with oxygen ions (Figs.…”
Section: Resultsmentioning
confidence: 99%